Bioaccumulation Patterns of Trace Elements in Jellyfish (Crambionella orsini and Cassiopea andromeda) from Northwestern Coastal Waters of the Persian Gulf - Yousef Darvishi; Hamidreza Pourkhabbaz; Paolo Pastorino; Giuseppe Esposito; Mahdi Banaee; Caterina Faggio (Journal of Marine Science and Engineering)
Trace element pollution in the Persian Gulf originates from industrial activities, urbanization, shipping, and oil extraction, leading to accumulation in sediments, water, and marine life such as jellyfish. This study investigated trace element bioaccumulation in two jellyfish species, Crambionella orsini and Cassiopea andromeda, across different locations. Jellyfish samples were collected from the Mahshahr and Dilam ports, and their trace element concentrations were analyzed using inductively coupled plasma mass spectrometry (ICP-MS). The study revealed no significant differences in trace element concentrations between C. orsini and C. andromeda. However, levels of copper, iron, manganese, and nickel were significantly higher in specimens from Mahshahr compared to those from Dilam. No significant differences were observed for cadmium, mercury, vanadium, tin, magnesium, and selenium across sites. Lower concentrations of lead, arsenic, zinc, and cobalt were found in C. orsini from Dilam compared to Mahshahr. Additionally, the study found no significant correlation between trace element concentrations in the water and their accumulation in jellyfish bodies. These findings offer valuable insights into the distribution and bioaccumulation of trace elements in jellyfish populations across different marine environments in the Persian Gulf.